Relevansi Jurnalistik sebagai Kontrol Sosial di Masyarakat dan Penanaman Ekstrakulikuler di Sekolah Dasar - Doni Saputra; Melva Zainil (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Until today, many individuals remain unaware of the core subjects explored by reporters and journalists. Journalism, which plays a vital role as a form of social control within society, ideally should be introduced from an early age. Developing strong journalistic writing abilities is a gradual process and cannot be achieved instantly. Therefore, this journal seeks to examine the extent of journalism’s impact and assess the level of understanding that elementary school students have in this area. This topic falls within the broader scope of Social Studies and Cartography.